2012
DOI: 10.9790/1684-0130110
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi integrated Least Square Support Vector Machine an alternative to Artificial Neural Network analysis of electrochemical machining process

Abstract: :The important performance parameter such as material removal rate (MRR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Shaban et al [17] diagnosed the machining outcome by a logical analysis of data for evaluation of product finishing quality and geometric profile by considering process parameters. Shi et al [18] have studied the characteristics of drilling in real time to detect influx and loss during machining operations using random forests and support vector machine. e most likely used algorithm in these studies is RF and SVR.…”
Section: Grinding Operationmentioning
confidence: 99%
“…Shaban et al [17] diagnosed the machining outcome by a logical analysis of data for evaluation of product finishing quality and geometric profile by considering process parameters. Shi et al [18] have studied the characteristics of drilling in real time to detect influx and loss during machining operations using random forests and support vector machine. e most likely used algorithm in these studies is RF and SVR.…”
Section: Grinding Operationmentioning
confidence: 99%
“…Shaban et al [17] diagnosed the machining outcome by a logical analysis of data for evaluation of product finishing quality and geometric profile by considering process parameters. Shi et al [18] have studied the characteristics of drilling in real time to detect influx and loss during machining operations using random forests and support vector machine. e most likely used algorithm in these studies is RF and SVR.…”
Section: Grinding Operationmentioning
confidence: 99%
“…It was concluded that the adopted model would be suitable for prediction of different surface characteristics with minimum mean absolute percentage error (MAPE). Nayak and Tripathy [19] applied multi-layer feed forward neural network (MFNN) and LSSVM techniques to predict MRR and SR values in an ECM process. Based on mean square error (MSE) values, it was propounded that LSSVM with RBF kernel function would outperform MFNN approach with respect to prediction accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%